Every cloud has a silver lining - Exploring the dark side of value co-creation in B2B service networks - Ilma Nur Chowdhury; Thorsten Gruber; Judy Zolkiewski (2016)
© 2016. This research explores the dark side of value co-creation (VCC) in B2B service networks. Whilst VCC is attracting a great deal of academic attention and a number of studies have highlighted the benefits of VCC, researchers often fail to consider the potentially negative consequences of VCC, especially in the context of business networks. This study explores the negative aspects associated with VCC in advertising service networks and identifies role conflicts and ambiguity, opportunism and power plays on the dark side of VCC. Tensions created by role conflicts during VCC interactions are highlighted. Also sharing of responsibilities during VCC can result in managers having a lack of clarity about what is expected of them, leading to role ambiguity and misunderstandings between firms. Managers engaging in VCC display weak-form opportunistic behaviors. These softer forms of opportunism are found to be tolerated and almost expected within long-term relationships. This research suggests that the exertion of power often shapes VCC activities within the advertising service network. Power plays are used as a means to mobilize appropriate resources and to influence network actors to adhere to value co-creation objectives. The presence of role conflicts, role ambiguity, opportunistic behaviors and power plays indicate that there is indeed a dark side to VCC that is currently omitted from existing VCC frameworks. A further contribution of our study is to highlight that a bright-dark dichotomy does not fully describe the complexity of VCC in B2B service networks and we show how the dark side may lead to positive outcomes.